Semisynthetic teicoplanin derivatives with dual antimicrobial activity against SARS-CoV-2 and multiresistant bacteria - Bereczki, Ilona; Vimberg, Vladimir; Lőrincz, Eszter; Papp, Henrietta; Nagy, Lajos; Kéki, Sándor; Batta, Gyula; Mitrović, Ana; Kos, Janko; Zsigmond, Áron; Hajdú, István; Lőrincz, Zsolt; et al. (Scientific reports, 2022)
Patients infected with SARS-CoV-2 risk co-infection with Gram-positive bacteria, which severely affects their prognosis. Antimicrobial drugs with dual antiviral and antibacterial activity would be very useful in this setting. Although glycopeptide antibiotics are well-known as strong antibacterial drugs, some of them are also active against RNA viruses like SARS-CoV-2. It has been shown that the antiviral and antibacterial efficacy can be enhanced by synthetic modifications. We here report the synthesis and biological evaluation of seven derivatives of teicoplanin bearing hydrophobic or superbasic side chain. All but one teicoplanin derivatives were effective in inhibiting SARS-CoV-2 replication in VeroE6 cells. One lipophilic and three perfluoroalkyl conjugates showed activity against SARS-CoV-2 in human Calu-3 cells and against HCoV-229E, an endemic human coronavirus, in HEL cells. Pseudovirus entry and enzyme inhibition assays established that the teicoplanin derivatives efficiently prevent the cathepsin-mediated endosomal entry of SARS-CoV-2, with some compounds inhibiting also the TMPRSS2-mediated surface entry route. The teicoplanin derivatives showed good to excellent activity against Gram-positive bacteria resistant to all approved glycopeptide antibiotics, due to their ability to dually bind to the bacterial membrane and cell-wall. To conclude, we identified three perfluoralkyl and one monoguanidine analog of teicoplanin as dual inhibitors of Gram-positive bacteria and SARS-CoV-2.
Keywords: Teicoplanin; Antiviral Agents; glykopeptidy; kathepsiny; Fluorocarbons; Humans; grampozitivní bakterie; lidé; Glycopeptides; SARS-CoV-2; Cathepsins; antibakteriální látky; Anti-Bacterial Agents; teikoplanin; Gram-Positive Bacteria; antivirové látky; COVID-19; fluorokarbony